Hume and the contention of superstitions - Belaúnde Barriga, José (1998)
This paper proposes an interpretation of the renowned last section of Hume's Natural History of Religion, after examining this work and its relations with some of his other works. The aim of this study is to give the clues to understanding Hume's critique of a rationally founded natural religion. The paper mainly contends that Hume destroys the basis for a rational religion independent or autonomous regarding superstition. He does so by means of a historical analysis of religious belief's process embedded in human nature's principies. All forms of religion are, therefore, some form or other of superstitious belief.